In search of beauty: António Botto's exile - Fernandes, Maria Lucia Outeiro [UNESP] (Univ Estadual Paulista-unesp, 2024)
Botto's aestheticism, abundantly emphasized by two of the critics most committed to pointing out the qualities of his poetry, Fernando Pessoa and Jose Regio, constitutes one of the most relevant aspects of his lyricism and stems from the desire to create beauty through art. To this incessant search for beauty corresponds a constant experience of exile. The purpose of this presentation is to highlight at least three different meanings for both the term beauty and the term exile invoked in the title. Both can be read in a more abstract sense of an ideal of life, which hovers above the hardships of the real world. Both can be related to the poet's work, in search of a singular language that effectively expresses his lyrical identity, his worldview and aesthetically identifies his work. And both can be related to the search for an effective space in which a human being seeks to find the necessary conditions for a dignified life, even far from his country of origin. All these connotations will be woven into this text.
Keywords: Antonio Botto; Exile; Aestheticism; Homoeroticism; Portuguese lyric poetry